2022
DOI: 10.1007/s11162-022-09703-w
|View full text |Cite
|
Sign up to set email alerts
|

Social Inequality in Dropout from Higher Education in Germany. Towards Combining the Student Integration Model and Rational Choice Theory

Abstract: Students from a lower socioeconomic background have a higher risk of dropping out of higher education. The underlying mechanisms of this association between socioeconomic background and higher education dropout are not well understood. Previous research in higher education has followed Tinto’s model of academic and social integration to explain dropout but has largely neglected social inequality therein. In contrast, social stratification research draws on rational choice theory to explain social inequality in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 72 publications
3
17
0
Order By: Relevance
“…Current research supports this (Allensworth & Clark, 2020). Furthermore, socioeconomic status (SES) would be a worth control variable due to its effects on motivation (Jansen et al, 2022;Tucker-Drob et al, 2012), achievement (Sirin, 2005;Steinmayr et al, 2012;Tucker-Drob & Harden, 2012), and dropout (Müller & Klein, 2022;Mϋller & Schneider, 2013). However, accurate measures for SES are not available in our data.…”
Section: The Present Studymentioning
confidence: 93%
“…Current research supports this (Allensworth & Clark, 2020). Furthermore, socioeconomic status (SES) would be a worth control variable due to its effects on motivation (Jansen et al, 2022;Tucker-Drob et al, 2012), achievement (Sirin, 2005;Steinmayr et al, 2012;Tucker-Drob & Harden, 2012), and dropout (Müller & Klein, 2022;Mϋller & Schneider, 2013). However, accurate measures for SES are not available in our data.…”
Section: The Present Studymentioning
confidence: 93%
“…This has led some researchers to seek to integrate additional interpretive models with Tinto's, such as Müller and Klein (2022), who found that rational choice theory better helped to account for the role of social stratification in exacerbating attrition.…”
Section: Literature On Reasons For Non-completionmentioning
confidence: 99%
“…Comparatively few studies have focused on the area of social integration, although those that do have drawn attention to the negative impact of experiences of social isolation and disconnect from peer groups and the impact this can have on attrition (e.g., G. Johnes and McNabb, 2004; Müller & Klein, 2022; Smith & Naylor, 2002; Yorke, 1999). Most research on non‐completion has focused on academic preparedness and/or students' academic pre‐entry attributes, exploring the lack of academic integration (or “mismatch”) between students and the course and/or university in question (e.g., G. Johnes and McNabb, 2004)—or what others have termed the issue of student “preparedness” (e.g., Smith & Naylor, 2002; Yorke, 1999).…”
Section: Literature On Reasons For Non‐completionmentioning
confidence: 99%
See 2 more Smart Citations